Sosialisasi Pemasaran Digital UMKM Peternak Ayam Petelur di Dusun Rumbia, Kabupaten Lampung Selatan - Gita Audria Salsabila; Riky Andria; Irma Fitriyani; Muhammad Intan Intan Haris; Rangga Syatria; Shahnaz Rafika; Mahrinasari Mahrinasari; Roslina Roslina (I-Com: Indonesian Community Journal, 2024)
In 2022, according to BPS data, Lampung Province emerged as the largest producer of chicken eggs in Indonesia. Small and Medium Enterprises (UMKM) of egg farmers in Dusun Rumbia, Krawang Sari Village, Natar District, South Lampung Regency, face intense competition among egg traders. The 2023 cohort of Master of Management students from the University of Lampung undertook community service activities to assist these UMKM, particularly owned by Mr. Wasirun, to enhance their competitiveness through digital media utilization. The methods employed included situational analysis, interviews, discussions, and problem-solving. The outcomes included establishing Instagram and TikTok accounts for promotional purposes, developing a sales-oriented website to facilitate product purchases, and introducing safer and more hygienic packaging to attract consumers. Through these marketing developments and digitalization efforts, it is expected that the egg farming UMKM in Dusun Rumbia will increase productivity, gain broader recognition, compete effectively with competitors, and improve profitability.